Design implications of a new load introduction mechanism into concrete-filled steel tubular columns. (May 2016) - Mollazadeh, Mohammad H.; Wang, Yong C.
Abstract: This paper presents the design implications of a new load introduction mechanism into concrete-filled steel tubular columns (CFST) proposed by the authors recently. According to the new load introduction mechanism, the beam-column connection load is introduced into the composite column through the column length above and within the connection. Based on the new load introduction mechanism, for slender CFST column design, a "concrete strength reduction factor" should be used to account for incomplete load introduction, when calculating the CFST column cross-section flexural stiffness. For CFST columns under combined axial compression and bending, the concrete strength reduction factor should be used when calculating the compression resistance, but should be ignored when calculating the bending resistance because composite action is always guaranteed for bending of the CFST column. The most important implication of the new load introduction mechanism is that the concrete core above the connection should be designed to resist the additional compressive force introduced to the concrete core below the connection. A further implication is that for ambient temperature design, the steel contribution ratio (steel section plastic resistance/plastic resistance of the composite cross-section) of the top floor column should be at least 0.25. For fire resistance design, the steel contribution ratio of the top floor columns, those on the floor below the top floor, and those two floors below the top floor, should not be less than 0.5, 0.33, and 0.25 respectively.